High pressure processing of jackfriut (Artocarpus heterophyllus L.) bulb - Ng, Siang Keat (2018)
Conventional processing technology, particularly thermal processing, may extend the shelf life of fruits. However, there is always a risk of inducing negative effects to the fruits, especially in terms of colour and texture. The emergence of high pressure processing (HPP), a novel non-thermal processing technology, brings promising hope of extending the shelf life of fruits while at the same time, preserving the fresh fruit’s characteristics. However, little is known or published on the effect of HPP on tropical fruits such as jackfruit. Thus, the effect of HPP on the microbiological, physicochemical and enzymatic properties of jackfruit bulbs at different pressures and holding times was studied. The pressures and holding times used in this study were 300, 400, 500 and 600 MPa at 3, 5, 10 and 15 min, respectively. The aforementioned treatments significantly (p < 0.05) reduced the microbial load to non-detectable level. However, the HP-treated samples exhibited no significant differences (p > 0.05) in terms of the proximate composition and ΔE indicator of total colour difference. HPP significantly (p < 0.05) increased the hardness and chewiness of the treated samples. In terms of enzymatic property, polygalacturonase (PG) and pectin esterase (PE) contents were significantly (p < 0.05) reduced by HPP. These results suggested that HPP had successfully inactivated the vegetative microorganisms while at the same time, retained the physicochemical properties of the jackfruit bulbs. An optimized pressure (500 MPa) and holding time (5 min) were then selected to process jackfruits bulbs packed using vacuum skin (VS) and vacuum nylon (VN) packaging. The samples were then stored at chilled temperature (4 °C) for shelf life study. HPP significantly (p < 0.05) increased the shelf life of VS- and VN-packed jackfruit bulbs to 60 days during chilled storage. In terms of colour stability during storage, both VSand VN-packed HP-treated jackfruit bulbs exhibited no significant differences (p > 0.05) in terms of L*, a*, and b* values. Also, the VS- and VN-packed HP-treated samples exhibited no significant differences (p > 0.05) in terms of texture and enzyme activity. However, the sensory evaluation carried out among 48 panellists showed that there were significant differences (p < 0.05) between the untreated and HP-treated jackfruit bulbs. The aforementioned results had proven that a HPP treatment of 500 MPa for 5 min could successfully extend the shelf life and retain the physicochemical properties of jackfruit bulbs, regardless of the types of packaging used.